2013
DOI: 10.1192/pb.bp.113.042945
|View full text |Cite
|
Sign up to set email alerts
|

Patients' awareness of the mental health tribunal and capacity to make requests

Abstract: Aims and methodTo evaluate patient awareness of the mental health tribunal and identify any association between capacity to request a tribunal and frequency of completed hearings. A cohort of detained patients within a secure hospital were assessed and data for past tribunals evaluated by presence of capacity and mode of application.ResultsOf the 65 patients evaluated, 78% were aware of the tribunal's power to discharge, 14% were aware of its power to recommend leave and 4% were aware of its power to recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Quantitative studies highlight gaps in knowledge and understanding about the mental health tribunal process and accompanying statutory rights. Galappathie, Harsh, Thomas, Begum, and Kelly () observed that out of 65 evaluated cases in England, only 70% of patients were aware of at least one way that they could request a tribunal. Similarly, a study conducted in Ireland found that 73% of informants were aware that they could appeal the decision (O'Donoghue et al, ) and this percentage was found to be slightly higher, at 78%, in a Western Australian study (Rolfe, Sheehan, & Davidson, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative studies highlight gaps in knowledge and understanding about the mental health tribunal process and accompanying statutory rights. Galappathie, Harsh, Thomas, Begum, and Kelly () observed that out of 65 evaluated cases in England, only 70% of patients were aware of at least one way that they could request a tribunal. Similarly, a study conducted in Ireland found that 73% of informants were aware that they could appeal the decision (O'Donoghue et al, ) and this percentage was found to be slightly higher, at 78%, in a Western Australian study (Rolfe, Sheehan, & Davidson, ).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Although some studies indicated that being able to attend the tribunal in and of itself was beneficial (Livingston et al, ; Ng et al, ), this was undermined by practices that silenced individual voice within proceedings (Beaupert & Vernon, ; Carney & Tait, ). This is exacerbated by a lack of awareness among individuals about their legal rights, further preventing them from actively participating in decision‐making (Galappathie et al, ; O'Donoghue et al, ). Although different jurisdictions offer a range of mechanisms to support patient representation, the current evidence demonstrates that, overall, this is inadequate in securing individual rights, with low levels of legal and advocacy representation being particularly problematic.…”
Section: Discussionmentioning
confidence: 99%
“…which could be taken as a proxy marker of their cognitive ability. A more recent study that explored the association between capacity to request a tribunal and frequency of completed tribunal hearings found that patients with capacity received more completed hearings per year than those without, both overall, and by patient application (Galappathie, Harsh, Thomas, Begum, & Kelly, ). This case study presents a woman with Down's syndrome who was detained under the MHA and who lacked capacity to challenge their detention.…”
Section: Introductionmentioning
confidence: 99%